2003
DOI: 10.1002/ijc.11246
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of hepatoid adenocarcinoma of the stomach:Molecular evidence of identical origin with coexistent tubular adenocarcinoma

Abstract: Hepatoid adenocarcinoma of the stomach is a highly malignant neoplasm. Most gastric hepatoid adenocarcinomas coexist with tubular adenocarcinoma. However, the relationship between hepatoid adenocarcinoma and tubular adenocarcinoma is still unclear. In the present study, the characteristics of the coexistent tubular adenocarcinomas were determined by examining their profiles of mucin production. Subsequently, molecular pathological techniques were applied to determine the clonality of 15 mixed hepatoid and tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…Oftheothertumourmarkers,especiallyCEAisoftenproducedbyHAC.PositivityforCEAwasobservedin50-100% of all published cases, occurring in all HAC of the pancreas [27,28],ovaries,andfallopiantube [21,[29][30][31][32][33][34][35][36],in86%ofthe gallbladdercases [10,22,23,37,38],andin51%ofthegastric HAC [7,8,10,11,24]. Our patient had normal CEA serum concentrations,butthetumourcellswereweaklystainedby CEAinconcordancewiththeotherpublishedHACcaseof theperitonealcavity [15].Noticeablefordiagnosticreasonsis thepositivityforCEA,AFP,andCA125orthedetectionof elevatedserumlevelsofCA125inovarianHAC [21,29,[31][32][33][34][35][36].TheCEAstainingis,however,oflittlevaluefordifferentiationbetweenHACandHCC,asthemajorityofHCCare alsoCEA-positive [39].…”
Section: Resultsmentioning
confidence: 99%
“…Oftheothertumourmarkers,especiallyCEAisoftenproducedbyHAC.PositivityforCEAwasobservedin50-100% of all published cases, occurring in all HAC of the pancreas [27,28],ovaries,andfallopiantube [21,[29][30][31][32][33][34][35][36],in86%ofthe gallbladdercases [10,22,23,37,38],andin51%ofthegastric HAC [7,8,10,11,24]. Our patient had normal CEA serum concentrations,butthetumourcellswereweaklystainedby CEAinconcordancewiththeotherpublishedHACcaseof theperitonealcavity [15].Noticeablefordiagnosticreasonsis thepositivityforCEA,AFP,andCA125orthedetectionof elevatedserumlevelsofCA125inovarianHAC [21,29,[31][32][33][34][35][36].TheCEAstainingis,however,oflittlevaluefordifferentiationbetweenHACandHCC,asthemajorityofHCCare alsoCEA-positive [39].…”
Section: Resultsmentioning
confidence: 99%
“…Kishimoto and associates [6] suggested that HAC develops from tubular or papillary adenocarcinoma, which tends to be detected superficially in the tumor. Akiyama and coworkers [7] found the adenocarcinomatous and hepatoid components to be of monoclonal origin, with identical patterns of genetic alteration. In addition, those investigators analyzed the cellular phenotype of these tumors using mucin histochemical methods and found that the adenocarcinomatous components expressed the intestinal phenotype.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, those investigators analyzed the cellular phenotype of these tumors using mucin histochemical methods and found that the adenocarcinomatous components expressed the intestinal phenotype. However, no mention was made of the cellular mucin phenotype of the hepatoid components [7]. Analysis of the cellular phenotype is considered useful for understanding the genesis and biological behavior of tumors [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Kishimoto et al proposed that gastric carcinoma might acquire hepatic differentiation during the tumor progression, "HACS transdifferentiation" [56]. Akiyama et al demonstrated that the hepatoid component exhibited exactly same patterns of chromosome X inactivation, p53 gene mutation, the level of p53 expression, and loss of heterozygosity with conventional adenocarcinomatous component of HACS [57]. These findings suggest a monoclonal origin of both glandular and hepatoid elements of HACS and support "HACS transdifferentiation" as the most accepted histogenesis.…”
Section: Hepatoid Adenocarcinomamentioning
confidence: 93%